@LeakyNun @LeakyNun Alright, suppose that we have a function $f:G \times G \to Y$ and we have a functional equation $$ \forall x,y,z \in G \; f[f(x,y),z]=f[x,f(y,z)]$$ and we want to prove that $$\forall x,y \in G \; f(x,y) \in G.$$
Let's take arbitrary $x,y \in G$ and $z=x$ then by associativity we have
$$f[f(x,y),x] = f(x,f(y,x)]$$
Now the notation $f(x)=y$ means that $(x,y) \in f$
thus we conclude that
$$ [(f(x,y),x),\; f(x,f(y,x))] \in f \subset (G\times G)\times Y$$
that is, $\exists u \in (G\times G)$, $\exists v \in Y$ such that